Impact of chemotherapy on gastrointestinal functions and the enteric nervous system. (November 2017) - Escalante, Jonathan; McQuade, Rachel M.; Stojanovska, Vanesa; Nurgali, Kulmira
Highlights: Chemotherapy before or after surgery is the main treatment for colorectal cancer. Gastrointestinal toxicity is a severe side-effect of chemotherapy. Chemotherapy-induced diarrhea and constipation persist long after treatment. Chemotherapy-induced enteric neuron damage leads to gastrointestinal dysfunction. Enteric neurons are a potential therapeutic target for chemotherapy toxicity. Abstract: Chemotherapy is the main treatment for many cancers, including colorectal cancer, a type of cancer with some of the highest prevalence and mortality rates worldwide. Although chemotherapeutic drugs have greatly improved the survival rates of cancer patients, there are many side-effects associated with their use. The gastrointestinal side-effects of chemotherapy often lead to dose reduction or even discontinuation of treatment, which in turn affects the clinical outcome. Gastrointestinal side-effects, such as chemotherapy-induced diarrhea and constipation, may persist many years after treatment, greatly reducing quality of life. Current treatments for these side-effects have many adverse effects themselves; therefore, new approaches are needed to address this problem. Changes in the enteric nervous system located within the gastrointestinal tract and controlling its functions have been implicated in many disorders. Recent studies providing insight into the association between chemotherapy-induced damage to enteric neurons and gastrointestinal dysfunction have highlighted the enteric nervous system as a potential therapeutic target to alleviate chemotherapy-induced toxicity which may improve both clinical outcomes and the quality of patients' lives.